Clinical and Laboratory Findings of 12 Children with Invasive Meningococcal Disease in Pediatric Intensive Care Unit - Eylem Kiral; Ayse Filiz Yetimakman (Critical Care Research and Practice)
Introduction. Invasive meningococcal disease (IMD) is a serious infectious disease requiring stay in a pediatric intensive care unit (PICU) that continues to be associated with high morbidity and mortality rates. Prompt recognition, early antibiotic therapy, and aggressive supportive therapies can reduce mortality. We aimed to assess the clinical and laboratory characteristics of children with IMD. Patients and Methods. We retrospectively evaluated the medical records of 12 children with IMD requiring PICU stay between January 2018 and July 2019. Results. We followed up 12 patients (five girls and seven boys, 5–168 months of age, and four below one year of age) with IMD (nine patients have meningococcemia with meningitis, and three patients have meningococcemia) in PICU. All children were previously healthy and have not received meningococcal vaccines. Their pediatric risk of mortality (PRISM) scores varies between 5 and 37, four of the patients required mechanical ventilation, and the predicted mortality was 39% at admission. Seven patients had catecholamine refractory septic shock and disseminated intravascular coagulation (DIC). Three of the patients required extracorporeal treatment. The predominant serogroup is Men B (5/12). The mortality rate was 16.6% with early use of antibiotics, fluids, and other interventions. Conclusion. Mortality related to IMD is higher among children with severe meningococcemia despite early interventions in PICU. Routine use of meningococcal vaccines during childhood would be a better strategy for controlling IMD in both developing and developed countries.